Immunohistochemical Detection of Human Papillomavirus in Cervical Cancer - Rengifo, Eduardo (2000)
OBJECTIVES: To establish the prevalence of Human Papillomavirus (HPV) in pre-malignant lesions and invasive cervical lesions, and to assess the sensitivity and specificity of inmunohisto- chemical method to detect HPV antigens with respect to the citologic, colposcopic and anatomopathologic studies. MATERIAL AND METHODS: Cervical biopsy samples were taken under colposcopy among 91 women from Lima, who had a previous abnormal cytologic control. Results of their citologic, colposcopic and biopsy samples, as well as immunohistochemical detection of viral antigens were recorded. RESULTS: HPV was diagnosed 39/91 (43%) by cytologic, 57/91 (63%) by colposcopic, and 78/91 (86%) by histologic methods. HPV antigen expression positivity was 53/91 (56%) by immunohistochemistry. High grade intraepiteliary scamous lesions (ISL) were more frequent than low grade ISL. CONCLUSIONS: Prevalence of HPV among cervical cancer and ISL was high. We considered that immunohistochemical method is not appropriated to HPV infection screenings due to its low sensitivity and specificity.